The Fourier transform infrared spectroscopy from Diplazium esculentum and Rivina humilis analysis to reveals the existence of necessary components in oil palm plantations of Ganoderma boninense control - Wismaroh Sanniwati Saragih; EDISON Purba; Lisnawita LISNAWITA; MOHAMMAD BASYUNI (Society for Indonesian Biodiversity, 2021)
Abstract. Saragih WS, Purba E, Lisnawita, Basyuni M. 2021. The Fourier transform infrared spectroscopy from Diplazium esculentum and Rivina humilis analysis reveals necessary components in oil palm plantations of Ganoderma boninense control. Biodiversitas 22: 3645-3651. The Fourier transform infrared spectroscopy (FTIR) has been widely utilized for biological samples and biomolecular characterization. We aim to identify Ganoderma boninense through FTIR and obtain a functional group that can facilitate early basal stem rot detection. Here, positive control (KP) was not inoculated with G. boninense and negative control (KN) was inoculated with G. boninense. However, the treatment samples, Diplazium esculentum leaf extract, Rivina humilis leaf extract, and fungicide treatment, were not inoculated with G. boninense. The positive control oil-palm leaf samples exhibited spectral bands similar to those in the D. esculentum extract, R. humilis extract, and fungicide treatment. Strong bonds were observed at wavelengths 3379 cm-1, 2927 cm-1, 1639 cm-1, and 1056 cm-1. Others were moderate to weak, except the negative control samples with strong bonds at 2044 cm-1. This indicates amine N-H functional groups, alkane functional group C-H, functional group alkene C=C, C-O, functional group ester, and functional group isothiocyanate N=C=S (C4H5NS or CH2 = CHCH2N=C=S). The FTIR plot result denotes G. boninense through N=C=S Isothiocyanate functional group presence at 2140-1990 cm-1. This unique structure is only found in infected oil-palm leaf tissues of G. boninense. Our study suggests that FTIR spectroscopy is more beneficial than conventional methods in early detection of G. boninense infection in oil palm.